الأسالیب والتقنیات المستخدمة فى تصمیم المواقع الالکترونیة المحمولة : دراسة تقییمیة لتصمیمات مواقع المکتبات المصریة المتاحة على الشبکة العنکبوتیة العالمیة - د. أحمد حسین بکر المصرى (المجلة الدولية لعلوم المكتبات والمعلومات)
The study aims to identifying the modern techniques used in designingand developing mobile websites and measuring the readiness of the EgyptianLibraries Website Designs for the requirements of making them available andbrowsing their content and services through mobile devices to the users'audience, based on the Descriptive Methodology in determining the currentsituation and Its data collection, processing, and analysis of its technicalcomponents provide an accurate analysis of the quality of its performance and itsaccessibility per successful practices in mobile websites.The study relied on collecting its information and analyzing its elementson a checklist that included (60) variable elements that were selected from thepublished literature in mobile website technologies, as well as what was includedin the technical tools used for testing the technical designs of the EgyptianLibraries Websites available on the World Wide Web. The study revealed that(32) websites are available for Egyptian libraries that are not accessible via theweb and that (59%) of them are configured to browse and display their contentsin a compatible way with mobile devices.The study concluded with several Recommendations addressed to thedesigners and developers of Egyptian library web sites, scientific departments forlibrary and information studies in Egyptian universities, and finally the EgyptianAssociation for Library and Information (ELA) as the institution for thedevelopment sector of libraries and information in Egypt.